Important areas and conservation sites for a community of globally threatened marine predators of the Southern Indian Ocean. (June 2019) - Heerah, K.; Dias, M.P.; Delord, K.; Oppel, S.; Barbraud, C.; Weimerskirch, H.; Bost, C.A.
Abstract: In the Southern Ocean, the impact of environmental changes and increasing human encroachment is causing declines in several populations of seabirds. Amsterdam island (77°33′E; 37°50′S) hosts some emblematic but globally threatened seabird species with alarming population trends. In 2017, concerns about Amsterdam Island's marine biodiversity led to the extension of a marine reserve to the boundaries of the exclusive economic zone (EEZ). Nevertheless, it is unknown whether this protected area is sufficiently large to encompass the most important foraging hotspots of the threatened seabirds, particularly during key stages of their life cycle (e.g. breeding period). We analysed movements of four threatened seabird species using a tracking dataset acquired over several breeding seasons from Amsterdam Island: Amsterdam albatross Diomedea amsterdamensis, sooty albatross Phoebetria fusca, Indian yellow-nosed albatross Thalassarche carteri and northern rockhopper penguin Eudyptes moseleyi . Our objectives were threefold: (1) characterise the at-sea distribution of the above-mentioned populations and delineate the marine Important Bird and Biodiversity Areas (mIBAs) triggered by them; (2) assess the potential threat at-sea by quantifying the overlap between seabird distribution and longline fishing efforts; (3) evaluate the coverage of identified mIBAs by marine protected areas and suggest complementary conservation actions. The identified important areas fell within the boundaries of the EEZ, but vastly exceeded the former reserve. Thus, our results reinforce the justification of the recent expansion of the reserve to the boundaries of the EEZ. However, overall seabird distributions extended beyond the EEZ (5 to 50% of the locations) and we found substantial overlap with longline fishing in the high seas. Our results provide a spatio-temporal envelope of where and when bycatch mitigation and observer coverage of longline fisheries should be mandated and enforced.